Paradigma Baru Sponsor sebagai Mitra Penyelenggaraan Event - Evelina, Lidia (Bina Nusantara University, 2011)
The goals of this article is to know why sponsorship only to be viewed as sources of funding to implement the public relation events or marketing communication events. Method used in this article is qualitative method research to be based on observation, library study and content analysis. The result of this research seems that change happened in role of sponsorship from only fund source to become a partner of cooperation (mutual symbiotism) between sponsor and event organizer. This article exploring the change of sponsorship concept from only looking for sponsor as an activity of fund mobilitation to become a partnership cooperation between event organizer and sponsor company. The mean of sponsor itself beside the fund supporter, they are also a side who takes mutual benefit from the cooperation. Conclusion, any close relationship (mutual benefit) between two sides who take cooperation in event implementation (sponsor and event organiser).